Упростите выражение (a+1)(a^2+1)(a^4+1)(a^8+1)(a^16+1)(a^32+1) Должно получиться (a^64 -...

0 голосов
27 просмотров

Упростите выражение (a+1)(a^2+1)(a^4+1)(a^8+1)(a^16+1)(a^32+1)

Должно получиться (a^64 - 1)\(a-1)


Алгебра (230 баллов) | 27 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

Решите задачу:

(a+1)(a^2+1)(a^4+1)(a^8+1)(a^{16}+1)(a^{32}+1)=
\\\
=\frac{(a-1)(a+1)(a^2+1)(a^4+1)(a^8+1)(a^{16}+1)(a^{32}+1)}{a-1}= 
\\\ 
=\frac{(a^2-1)(a^2+1)(a^4+1)(a^8+1)(a^{16}+1)(a^{32}+1)}{a-1} =
\\\ 
=\frac{(a^4-1)(a^4+1)(a^8+1)(a^{16}+1)(a^{32}+1)}{a-1}=
 \\\
=\frac{(a^8-1)(a^8+1)(a^{16}+1)(a^{32}+1)}{a-1}= 
\\\
=\frac{(a^{16}-1)(a^{16}+1)(a^{32}+1)}{a-1}=
 \\\
=\frac{(a^{32}-1)(a^{32}+1)}{a-1}=\frac{a^{64-1}}{a-1}
(271k баллов)
0 голосов

Решите задачу:



\\\frac{(a-1)(a+1)(a^2+1)(a^4+1)(a^8+1)(a^{16}+1)(a^{32}+1)}{a-1}=
\\.
\\\frac{(a^2-1)(a^2+1)(a^4+1)(a^8+1)(a^{16}+1)(a^{32}+1)}{a-1}
\\\frac{(a^4-1)(a^4+1)(a^8+1)(a^{16}+1)(a^{32}+1)}{a-1}=
\\\frac{(a^8-1)(a^8+1)(a^{16}+1)(a^{32}+1)}{a-1}=
\\\frac{(a^{16}-1)(a^{16}+1)(a^{32}+1)}{a-1}=
\\\frac{(a^{32}-1)(a^{32}+1)}{a-1}=\frac{a^{64-1}}{a-1}



(1.9k баллов)